PENGEMBANGAN LEMBAR KEGIATAN SISWA MATA PELAJARAN FISIKA YANG DISESUAIKAN DENGAN KTSP RSBI PADA POKOK BAHASAN GERAK LURUS UNTUK SISWA SMP KELAS VII RSBI (Jurnal Penelitian Pendidikan Matematika dan Sains, 2011)
Abstract: The research about developing student worksheet of science in junior high school has been done. This research have objective to know of suitable student worksheet with the content standard and to know the effectiveness of student worksheet in teaching science with cooperative model. Focus problems is: how the effectiveness of student worksheet that have developed using cooperative model. Development of teaching tool using 4D model (except Disseminate) and designing tryout using one group pre-test-posttest design. The data analyzed using descriptive statistic and descriptive qualitative. The results of research, developing of student worksheet and lesson plan effective with with cooperative learning model. Based on the discuss results have obtained score of 3,6 – 4,00 its mean all of activity in learning process good and student worksheet have obtained score of 3 its mean good category. Students’ respond 84% 0,32 to 0,82 proportion. Students social skill shows being satisfied especially aspect of ask, discuss, cooperative and communicate. Students’ character shows being satisfied especially aspect of honest, responsible, accurately and discipline. Key words: KTSP RSBI, Students worksheet, Linier Motion, Effectiveness.